Results from the Teach For America 2015 National Principal Survey - Rudnick, Mollie (RAND Corporation, 2015)
The results of the 2015 National Principal Survey show the context in which Teach For America (TFA) corps members work, how principals perceive corps members, and how principals perceive their interactions with TFA. These findings can help TFA staff provide more-tailored supports to corps members, inform professional development, and continue to build relationships with the principals of schools in which corps members serve.